Palladium(II)-Catalyzed Three-Component Tandem Cyclization Reaction for the One-Pot Assembly of 4-Arylquinazolines - Wang, Zijuan; Chen, Wenteng; He, Chang; Zhang, Guolin; Yu, Yongping (Synthesis, 2020)
A one-pot method for joining three separate components leading to an assortment of 4-arylquinazolines (27 examples) in good to excellent yields is described. The method consists of a palladium(II)-catalyzed cascade reaction involving C(sp)–C(sp2) coupling followed by intramolecular C–N bond formation. The reaction was readily scaled up to gram quantity and successfully applied to the synthesis of a translocator protein (TSPO) ligand.
Keywords: 4-arylquinazolines; palladium(II) catalysis; one-pot assembly; tandem cyclization reaction; ligands